SIMULASI SISTEM REVERSE OSMOSIS BERBASIS MIKROKONTROLER PADA PEMBANGKIT LISTRIK TENAGA UAP - Furqon, Muhammad; Hamdhany, Tadjuddin; Dodu, Erwin (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2016)
The development of control systems has now reached a level that better facilitate the work of man. Most of control systems have been used in industrial companies.However, there is another thing that also have important rule in making easier the human's assignment which is in form of manual control, namely the simulation display system, installed on a device that is used to control theequipment using display on PC (Personal Computer) without facing them directly.This system has started to be implemented and applied by some modern industries. One example of the use of simulation display system is the construction of the simulation of reverse osmosis systems on PLTU (steam power plant) in order to facilitate the operator to run the simulation test. The problem statement created in this research was how to design the simulation display of reverse osmosis systems using the programming language of Macromedia flash 8, Delphi,ISIS Proteus, and Micro Pascal and then communicate it with the simulation of microcontroller based reverse osmosis systems. The result of this research is the simulation display of reverse osmosis systems which iscreated manually and automatically. The systemis communicated with the simulation of microcontroller based reverse osmosis systems where there are five motors and three tanks.The motors will drain the water of each tanks through the filtration process. Later on, the pure water as the final result of the filtration process will be used for steam cycle process in the boiler. Keywords: Simulation display, Reverse Osmosis Systems, Macromedia flash 8, Delphi, ISIS Proteus. I. P